Formulation and evaluation of encapsulating acetaminophen into monodisperse biodegradable nanoparticles by nanoprecipitation method: factorial design and characterisations - Lum, Li Lian (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The invention of encapsulation of drug into nanoparticles into a monodisperse, biodegradable nanoparticles enhances the drug delivery systems. The biodegradable nanoparticles are prepared by nanoprecipitation method. The acetaminophen-loaded nanoparticles are formed for the stabilization and delivery of nanoparticles to the targeted area. Besides that, the new, optimum formulation of encapsulated Acetaminophen nanoparticles can be identified. The design of experiment approach is used in the project to find the suitable range of parameters to produce nanoparticles with optimum range of particle size. Different analytical techniques such as FTIR, and UV-Vis are used to characterize the physic chemical properties of the nanoparticles formed. The Factorial Design 25 are at optimum with concentrations of PCL at 6 g L-1, paracetamol amount of 20 %w/w, organic phase/ aqueous phase of 2:1, PVP surfactant concentrations of 0.5 % and speed of 1200 rpm. The ANOVA of Factorial design is at regression, R2 of 0.9633. The FTIR spectrum of pure PCL, pure PCM, PCL and PCM, encapsulated nanoparticles were tested to identify whether the PCM is successfully encapsulated into the PCL. Future study of acetaminophen-loaded nanoparticles can be done on the kinetic study of nanoparticles for potential pharmaceutical application.